Bilateral exudative retinal detachments after subretinal gene therapy with voretigene neparvovec-rzyl for RPE65 Leber Congenital Amaurosis - Alcina K. Lidder; Stephanie Choi; Yasha S. Modi; Scott E. Brodie; Janet L. Davis; Ninel Z. Gregori; Byron L. Lam (American Journal of Ophthalmology Case Reports, 2023)
Purpose: To report panuveitis with exudative retinal detachments in a healthy 27-year-old woman with biallelic mutations in the RPE65 gene, who underwent bilateral sequential gene therapy with subretinal administration of voretigene neparvovec-rzyl. Observations: Visual acuity improved for 30 days after surgery as oral corticosteroids were tapered. At postoperative week 6, vision declined due to sudden onset uveitis and exudative retinal detachments in both eyes. HLA Class II typing revealed the haplotype associated with sympathetic ophthalmia and Vogt-Koyanagi-Harada (VKH). The inflammation improved after corticosteroid, mycophenolate mofetil, and adalimumab therapy while vision remained poor. Conclusions and Importance: Surgically-induced sympathetic ophthalmia is a plausible explanation for the clinical findings; surgery of both eyes within one week would conceal the inciting eye. VKH or inflammation related to the gene therapy are other possible etiologies but severe bilateral panuveitis has not been reported with voretigene neparvovec-rzyl. Informed consent for gene therapy surgery should include a discussion of the rare complication of sympathetic ophthalmia following vitrectomy surgery.